Local forests' management bears fruit - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Local forest management in the Sahel. Towards a new social contract By P Kerkhof and edited by G Foley, SOS Sahel, London. 2000. 83 pp. ISBN 1 901459 28 4 Copies available on request.